Campus Tourism for Environmental Sustainability: A Mini Review - Orryel Jaunis; Fazilah Musa; Rosmalina Abdul Rashid (Corpus Publishers, 2022)
Deforestation is a global problem that has spread throughout the world’s forests. Uncontrolled urbanisation is a factor in destroying natural resources, which results in severe pollution, particularly in developing countries. The 2030 Agenda for Sustainable Development was launched in 2015 to establish sustainable cities and communities in response to the deteriorating situation. Education is an excellent method of boosting public awareness and knowledge about sustainability. As new urban tourism, campus tourism has grown in popularity over the previous two decades. Campus tourism should address this ongoing environmental issue by utilizing the institution as a knowledge-transfer platform for society. This article studies the available literature to understand the global phenomenon of campus tourism. Six components of campus tourism were identified through a review of the academic literature. Subsequently, this article emphasized the importance of contrasting Edutourism and campus tourism to dispel misconceptions. In conclusion, this mini review is intended to serve as a starting point for universities and colleges globally interested in establishing campus tourism for environmental sustainability